Time mental accounting and novice employees’ intertemporal choices: mediating effects of time management disposition and future self-continuity - Liu, Jie; Zhang, Mingwei; Yu, Tao; He, Lidong; Wu, Yuzhen; Pan, Xiaofu (Frontiers in Psychology, 2026)
IntroductionThis study examined how time mental accounting relates to intertemporal decision-making among novice employees and whether this relationship operates through time management disposition (TMD) and future self-continuity (FSC), drawing on Conservation of Resources theory.MethodsA nationwide sample of 597 early-career employees in China completed validated measures of time mental accounting (loss aversion, mental budgeting, and flexibility), TMD, and FSC, as well as eight binary intertemporal choice tasks contrasting smaller-sooner versus larger-later rewards. Correlations and structural equation modeling with bias-corrected bootstrapping were conducted, controlling for age, gender, and education.ResultsLoss aversion and mental budgeting were positively associated with TMD and FSC and negatively associated with smaller-sooner choices, whereas flexibility showed no significant associations. Mediation analyses indicated that the effects of time mental accounting facets on intertemporal choice were transmitted indirectly via TMD and FSC, with non-significant direct effects when mediators were included.DiscussionThe findings support a dual-path mechanism whereby structured time allocation and stronger future self-identity function as complementary resources that reduce short-term bias in novice employees’ intertemporal decisions.